Two dimensional roll forming simulation using plane strain elements with simplified roller contact definition - Muhammad Fikri, Che Manshor (2007)
In the industrial today, roll forming was used for large production run. In the roll forming process, the sheet metal of workpiece was feed into successive pairs or set of roller until the desired cross section profile was achieved. The purpose of this study is to do the simulation of roll forming using plane strain element with simplified roller contact definition and also to determine percentage of elastic recovery occur in the roll forming process and design of the roller. This simulation was conducted using ALGOR software which is software for Finite Element Analysis (FEA) to know in deep the relationship between the strain and elastic recovery. This simulation was use five set of roller to shape the sheet metal until it becomes the product. The results of this study show that the strain in the material had give the effect and implication to elastic recovery. From this study also it can help and give the basic idea to designer to control and reduce the elastic recovery in the roll forming process.